Environmental relevance of the platinum-group elements - Rauch, S.; Morrison, Greg (Mineralogical Society of Canada, 2008)
Platinum-group elements (PGE) are used in an increasing number of applications, and emissions are resulting in elevated environmental concentrations of these normally rare metals. Automobile exhaust catalysts, which use Pd, Pt, and Rh as active components, are the main source of PGE emitted into urban and roadside environments, and they contribute to a global increase in PGE concentrations. Emitted PGE are found in urban air and accumulate on the road surface and in roadside soil. Transport of PGE via stormwater is resulting in contamination of aquatic environments. There is now mounting evidence that a fraction of PGE in the environment is bioavailable, and potential uptake into the biosphere is raising concern over potential risks for humans and the environment.